The Meaning of Water Environment for Stilt Houses on the Musi Riverbanks, Palembang - Ari Siswanto; Ira Kusumawaty (Program Pascasarjana Universitas Sriwijaya, 2021)
Water functions are very diverse for humans for daily needs such as drinking water, bathing, agriculture, development, aesthetics and lowering temperatures. Palembang is a lowland area dominated by wetlands, tidal swamps and rivers. The types of houses on stilts on the banks of the Musi river are limas, gudang and Chinese stilt houses which are always associated with the water environment. The construction of roads replacing the role of rivers has realized that water environment has an important meaning for the house on stilts. The research objective was to explore the meaning of the water environment from various aspects for residents, stilt houses and their environment. The case study research method, taking field data, namely observation, photos, measurements and interviews with participants who are owners, residents and community leaders. Data and findings were analyzed and juxtaposed with images in the field. The road construction has eliminated part of the function of the river and influenced the change in orientation of the house on stilts. In conclusion, respect for water environment including rivers has decreased, causing the quality of the river to decline, and the house on stilts cannot take advantage of the existence of water environment optimally.